Few-walled carbon nanotubes derived from shoe waste plastics: effect of feedstock composition on synthesis, properties and application as CO₂ reduction electrodes - Chen, Wen Qian (2022)
This work investigates the chemical recycling of shoe waste plastics, i.e. polyurethane (PU) and ethylene-vinyl acetate (EVA) using a pyrolysis-chemical vapor deposition process over Fe/MgO catalyst. Results suggested PU facilitated highly selective production of few-walled CNTs with small diameters and narrow size distribution while EVA tended to yield multi-walled CNTs. The synergistic interactions between pyrolysis gases components from PU and EVA allowed facile tailoring of CNT size distribution by using either sorted PU and EVA or mixture (EVA/PU) in appropriate ratios. CNTs derived from pure PU or EVA/PU were more suitable in designing effective electrocatalysts for CO2 reduction with Faradaic efficiency of 85–95% and CO current density of >9 mA cm−2. This was because the presence of few-walled CNTs could enhance electrical conductivity and specific surface area without compromising the loading of active materials.